Four Ages of Professionalism and Professional Learning - Hargreaves, Andy (Teachers and Teaching, 2000)
This paper conceptualizes the development of teacher professionalism as passing through four historical phases in many countries: the pre-professional age, the age of the autonomous professional, the age of the collegial professional and the fourth age-post-professional or postmodern. Current experiences and perceptions of teacher professionalism and professionalization, it is argued, draw on all these ages. Conclusions are drawn regarding new directions in teacher professionalism, and the linking of professional projects to wider social movements for public education and its transformation.